Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5001/omj.2014.67
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing Patterns in Outpatient Emergency Clinics at Queen Rania Al Abdullah II Children's Hospital, Jordan, 2013

Abstract: Our results showed high consumption of antibiotics by emergency department pediatricians which highlight the importance for interventions to promote rational and judicious prescribing. An insight into factors influencing antibiotics prescribing patterns by military prescribers is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 16 publications
7
46
3
Order By: Relevance
“…These findings can be compared with a study conducted in Jordan (Al-Niemat et al 2014), which showed that out of 85% prescriptions with antibiotics, 88% prescriptions had one antibiotic, 11% had two and 1% had three antibiotics. Likewise in a Turkish study involving 39.4% prescriptions with antibiotics, 73.6% prescriptions had one antibiotic, 19.6% had two, 5.7% had three and 1.1% had four antibiotics (Erbay et al 2003).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…These findings can be compared with a study conducted in Jordan (Al-Niemat et al 2014), which showed that out of 85% prescriptions with antibiotics, 88% prescriptions had one antibiotic, 11% had two and 1% had three antibiotics. Likewise in a Turkish study involving 39.4% prescriptions with antibiotics, 73.6% prescriptions had one antibiotic, 19.6% had two, 5.7% had three and 1.1% had four antibiotics (Erbay et al 2003).…”
Section: Discussionmentioning
confidence: 73%
“…An Indian study showed that the highest prescribed antibiotics were cefixime (37.98%), ceftriaxone (7.97%), azithromycin (6.33%) and gentamicin (6.25%) (Khan et al 2011). In another study, azithromycin contributed the highest percentage share (97%) of the total antibiotics (Al-Niemat et al 2014). It is clear from this body of literature that the extent of antibiotic prescription is high but that there is considerable variation in the number and types of antibiotics selected to prescribe.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies on antibiotic appropriateness in emergency department settings are very limited and largely focused on in-patients and pediatrics age groups [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Several investigations showed difference in consumption and utilization of antibiotics from one country to another with an emphasis on emergency services. 10,11 It is based on antibiotics prescribing regulations and infectious diseases treatment guidelines. To the best of our knowledge there is no investigation in the KSA or Gulf and Middle East countries about antibiotics consumption at ER services.…”
Section: Introductionmentioning
confidence: 99%